A Muhammadiyah's International Expansion: A Case Study of Leadership Dynamics in Taiwan - Hariyadi, Eko; Alwi Eka Pranata, Muhammad; Amru Al Amin, Muhammad; Maulana, Muchsin; Hidayatullah Utomo, Azka; Jundan Labib, Muhammad (Universitas Muhammadiyah Yogyakarta, 2024)
This paper examines Muhammadiyah's establishment and growth as a prominent Islamic organization in Indonesia within the context of Taiwan. The analysis is centered on the Special Branch Leadership, a group dedicated to providing assistance to the Indonesian Muslim community in Taiwan. The study employs a literature review methodology to examine the personality, principles, and actions of Muhammadiyah. It employs a combination of academic literature and official records to gain insight into the organization's historical trajectory in Taiwan. This study examines the development of Muhammadiyah in Taiwan, beginning with its initial formation under the guidance of visionary leaders and culminating in its official establishment and subsequent growth. The text focuses on the organization's tangible locations, important divisions, cooperative projects, and influence on the community, explicitly emphasizing its dedication to comprehensive growth and assistance for Indonesian Muslims in Taiwan. As a result, the strong and thriving presence of Muhammadiyah in Taiwan serves as an exemplar of resilience, adaptability, and commitment to advancing Islamic principles and the community's well-being. This serves as a symbol of optimism and motivation for Muslims worldwide.